Роль попечителів навчальних округів у вирішенні кадрових питань університетами України (друга половина ХІХ – початок ХХ століття) - Таможська, Ірина Володимирівна; Tamozhska, Iryna Volodymyrivna (Луцьк : Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті проаналізовано організаційні засади, теорію та практику управлінської діяльності попечителів Одеського, Харківського та Київського навчальних округів другої половини ХІХ – початку ХХ століття. Установлено, що попечителі навчальних округів здійснювали зв’язок між університетами та Міністерством народної освіти для вирішення нагальних питань. Віднайдені матеріали дають змогу простежити як позитивні, так і негативні наслідки від розпоряджень попечителів навчальних округів. З’ясовано, що справи щодо розгляду кандидатур на вакантні посади в Університеті Св. Володимира, Новоросійському та Харківському університетах входила до компетенції попечителів або з їхніми рекомендаціями подавалися до розгляду Міністерства народної освіти. Відмічено, що попечителі контролювали науково-дослідницьку та педагогічну діяльність викладачів, а також здійснювали контроль за публікацією матеріалів протоколів і витягів із протоколів у періодичних виданнях, що висвітлювали актуальні для навчального закладу питання. Наголошено на тому, що розмір винагороди приват-доцентам узгоджувався керівництвом університетів із Міністерством народної освіти та попечителями навчальних округів. Підкреслено, що попечителі навчальних округів підтримували рішення членів учених рад щодо відмови надання кандидатам вакантних викладацьких посад на основі ідеолого-політичних чинників. Зроблено висновок про роль попечителі навчальних округів у структурі управління дореволюційними університетами України.

The organizational principles, theory and practice of the management activity of curators of Odesa, Kharkiv and Kyiv educational districts in the second half of the XIX – the beginning of the XX century are analyzed in the article. It is defined that the curators of educational districts carried out the connection between universities and the Minister of National Education to solve urgent issues. The found materials enable the possibility to trace both positive and negative consequences of the orders of the curators of educational districts. It is explored that cases for consideration of candidates for vacant posts in St. Volodymyr University, Novorosiysk and Kharkiv Universities were included into curators’ competence or were presented for consideration to the Ministry of National Education with their recommendations. It is observed that the curators controlled the scientific-research and pedagogical activity of university lecturers (giving to privat-associate professors the permission to conduct credits and teach medical and science disciplines that demanded research work; prohibiting strangers to be present at the introductory and demonstrative lectures of privatassociate professors or professors; providing opportunities for lecturers of the faculty only to attend master's lectures), they also controlled the publication of materials of the records and the extracts from the records of the Science Councils meetings in «Notes of the Imperial Novorosia University», «University News» and «Notes of the Imperial Kharkiv University», which revealed problems that were actual for the educational establishment. It is noted that the curators of educational districts took part in the meeting, which was held under the auspices of the Ministry of National Education, and also were members of the Commission that examined issues related to the improvement of the universities activities. The attention is drawn to the fact that the size of the privat-associate professors’ fees was agreed with the administrations of universities, with the Ministry of National Education and with the curators of educational districts. It is emphasized that the curators of educational districts supported the decisions of the Science Councils members to deny giving vacant teaching posts to the candidates based on the ideological and political factors. Conclusion is made about the role of the curators of educational districts in the management structure of the prerevolutionary universities of Ukraine.
The role of the curators of educational districts in solving staff issues of universities of Ukraine (the second half of the XIX – the beginning of the XX century)
Keywords: HUMANITIES and RELIGION; попечителі Одеського, Харківського та Київського навчальних округів; управління; кадрові питання; curators of Odesa, Kharkiv and Kyiv educational districts; management; staff issues